Modern innovative technologies in teaching English - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article highlights the importance given to foreign languages in continuing education in the Republic of Uzbekistan and the innovative technologies needed to study them. Teaching English to preschool and primary school children using innovative technology, intellectual games and interactive methods using unusual principles and pedagogical technologies, overcoming difficulties in learning English and becoming stronger the effective use of innovative technologies in the acquisition of knowledge.